PROPOSED GUIDELINES TO MINIMISE MULTI-DRUG RESISTANT TUBERCULOSIS TREATMENT DEFAULT IN A MULTI-DRUG RESISTANT UNIT OF LIMPOPO PROVINCE, SOUTH AFRICA - Chauke, T; Netshikweta, L; Netshandama, VO; Nyathi, L; Tshitangano, TG; FC, Olaniyi (African Journal of Infectious Diseases (AJID), 2018)
Background: The increasing prevalence and incidence of Multi Drug Resistant Tuberculosis (MDR-TB) is as a result of the defaulting of treatment by patients. Worldwide, several factors that contribute to patients defaulting to tuberculosis treatment protocol have been identified. This paper aims to develop guidelines to minimise the defaulting rate of MDR-TB patients in MDR unit of Limpopo Province. Materials and Methods: The study was conducted using a qualitative approach. Tesch’s open coding method of data analysis was adopted to analyse the data obtained. Reasoning strategies were employed in the development of the guidelines. These include analysis, synthesis, deductive reasoning and inductive reasoning. Synthesis strategy was used to construct relational statements. Results: The factors contributing to patients’ default from MDR-TB treatment were identified and organized into four themes. Guidelines were developed to address each factor and give recommendations on possible solutions. Conclusion: The guidelines that were developed concluded that co-operation amongst the Department of Health, health practitioners, patient, and family members can help in preventing the defaulting of treatment.